Analytical and FEA-based evaluation of natural frequencies of aircraft power turbine blades for resonance zone identification and comparative material suitability assessment - Pokhrel, Jivan; Pokharel, Kamal; Khadka, Rajiv Kumar (Journal of Innovations in Engineering Education, 2026)
Natural frequencies strongly influence the vibration response of aircraft power turbine blades operating at high rotational speeds and elevated temperatures. Resonance under such conditions can lead to excessive vibration, fatigue damage, and blade failure. In this study, the natural frequencies of a power turbine blade are evaluated using an analytical beam-based approach that includes centrifugal stiffening and temperature-dependent material properties. The analytical results are validated through finite element modal analysis. Three materials Titanium Alloys- Ti6Al4V, Inconel-738, and CM-247 LC are examined at an operating temperature of 850 °C and rotational speeds up to 32,000 rpm. The comparison shows good agreement between analytical and numerical results. The study highlights the influence of material stiffness degradation at high temperature and demonstrates that CM-247 LC offers the most stable vibrational performance under combined thermal and rotational loading.